Predictors of Appropriate Shocks and Ventricular Arrhythmia in Indonesian with Brugada Syndrome - Ardian Rizal; Sunu Budhi Raharjo; Dicky Armein Hanafy; Yoga Yuniadi (Majalah Kardiologi Indonesia, 2019)
Background :